Christmas in Winter Valley [large type] - Thomas, Jodi (Thomas, Jodi. Ransom Canyon romance, 2024)
"Cooper Holloway would take nature over people any day -- especially visiting relatives. That's why he's headed for a rustic cabin in remote Winter Valley, where he'll care for a herd of wild mustangs. But Cooper's plans are quickly thwarted by the arrival of two unexpected guests: one, a stranger in desperate need of his help, and the other, a very attractive young veterinarian. Elliott is busy trying to keep Maverick Ranch running smoothly with Cooper gone, which is no easy task with family visiting. And when a long-lost love suddenly reappears in his life, Elliott knows he'll have more than just books to balance this season. With a big, chaotic family Christmas around the corner and love blooming in surprising ways, the Holloway men will have to make big choices about the future -- just in time for the holidays."--